Conflicting Perspective on GenAI in Higher Education: A Qualitative Study of Student Use and Marker Responses in an ODeL Context - Mohale, Ntshimane Elphas (Studies in Learning and Teaching, 2026)
e surge of GenAI in higher education has sparked mixed reactions among students, markers, and scholars. Guided by Moore’s Transactional Distance Theory, this qualitative case study investigates conflicting perceptions of GenAI use in an ODeL context, where limited dialogue and increased transactional distance hinder effective communication. Data were collected through open-ended online questionnaires from students and structured evaluation forms from markers. Results show that students use GenAI to improve grammar, vocabulary, idea generation, and structural quality, which promotes cognitive development and helps overcome writer’s block and low confidence. However, students fear being stigmatised by markers and often self-censor due to unclear institutional policies. Markers, on the other hand, question the authenticity and depth of GenAI-incorporated content, viewing it as generic and lacking critical engagement. This leads to biased assessments, ethical dilemmas, and strained student–marker relationships, worsened by unreliable GenAI detection tools and the absence of institutional guidelines. The study concludes that GenAI’s influence on transactional distance depends on institutional readiness to integrate and regulate its use responsibly. Therefore, institutions should develop transparent GenAI policies, provide literacy training, and promote open dialogue to ensure fair assessment, reduce bias, and reframe GenAI as a transformative pedagogical tool rather than a threat.